2017
DOI: 10.2147/ijwh.s145383
|View full text |Cite
|
Sign up to set email alerts
|

Psychological burden among women with polycystic ovarian syndrome in Oman: a case–control study

Abstract: PurposePrevious studies in Euro-American populations have shown that women with polycystic ovarian syndrome (PCOS) have increased levels of “psychological burden”. While PCOS has been reported in Arab countries such as Oman, there is a dearth of studies of the occurrence of psychological burden among PCOS women in the Arab region. This study aimed to compare sociodemographic and clinical characteristics of PCOS women diagnosed with non-PCOS women and prevalence of severity of depression, anxiety and stress and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 41 publications
1
16
2
2
Order By: Relevance
“…The experiences of the participants of this study showed that adaptation to illness could emerge as a depressive mood in some adolescents. The diagnosis of PCOS has psychological ramifications 31. Depression and moodiness in adolescents and the appearance of a depressive mood have been argued to be associated with symptoms such as disturbed sleep, lethargy, restlessness, changes in appetite and weight, decreased motivation and concentration, decreased self-esteem and isolation 32.…”
Section: Discussionmentioning
confidence: 99%
“…The experiences of the participants of this study showed that adaptation to illness could emerge as a depressive mood in some adolescents. The diagnosis of PCOS has psychological ramifications 31. Depression and moodiness in adolescents and the appearance of a depressive mood have been argued to be associated with symptoms such as disturbed sleep, lethargy, restlessness, changes in appetite and weight, decreased motivation and concentration, decreased self-esteem and isolation 32.…”
Section: Discussionmentioning
confidence: 99%
“…Anxiety was the most prevalent psychological impairment noted in this research with prevalence rates of 63.4%. 17 Oman has geographic and cultural proximity to South Asia. Omani women may exhibit similar phenotypic expression of disease as in South Asian women due to shared genetic and socio-cultural factors and explains concordance of results.…”
Section: Resultsmentioning
confidence: 99%
“…Al-Fazari et al found that suboptimal nutritional and dietary practices are common among Omani women with PCOS compared to controls 27. Furthermore, we earlier reported higher rates of psychological burden indices among Omani PCOS women compared to controls 28. Despite this, the presence of oxidative stress among PCOS women in Oman has not been explored.…”
Section: Introductionmentioning
confidence: 89%